Culpability Dalam Penentuan Sanksi Tindak Pidana Penganiayaan yang Dilakukan Secara Tidak Sengaja - Insani, Nursolihi; Octaviyanti, Ary; Suhendar; Hanna Zafira, Siti (Rechtsregel : Jurnal Ilmu Hukum, 2024)
Guilt is one of the fundamental principles in criminal law, which states that a person cannot be punished in the absence of guilt. A person is considered guilty if their inner attitude can be regretted for committing an unlawful act. The concept of guilt is a juridical concept, not a moral or social concept. Determining sanctions for someone who does not intentionally commit a criminal act, of course, will be different from someone who does it intentionally. Therefore, in imposing sanctions must look at the inner attitude or intention of the perpetrator. The research method used is normative juridical, with a statutory approach, as well as legal doctrines to answer the problems that occur and in order to produce new arguments, theories or concepts as a basis for solving the problems at hand.